THE EFFECT OF MUDHARABAH FINANCING AND MUSYARAKAH FINANCING ON NET PROFIT (Case Study at Bank Jabar Banten Syariah Period 2018-2020): Akuntansi Syariah - Rahmawati Dwina Putri; Dian Hakip Nurdiansyah (Prodi Ekonomi Syariah Universitas Majalengka, 2022)
This research method uses a quantitative approach with secondary data in the form of the company's monthly financial statements, with the aim of testing the effect of mudharabah and musyarakah financing on the net profit of Bank Jabar Banten Syariah for the 2018-2020 period. The research sample used for this study used a sampling technique, where all 36 months of the population were used as samples. The analysis technique in this study uses multiple regression analysis and is processed using SPSS 16. The results show that mudharabah financing partially has a negative effect on net income because the value of Tcount is -2.381 < Ttable 2.034 and the sig value obtained is 0.023 <0.05. While partially musharaka there is no effect on net income based on the Tcount value obtained at 1.993 < Ttable 2.034 and the sig value has a value of 0.055 > 0.05. And two independent variables simultaneously have a significant effect on net income with a value of Fcount 3.367 > Ftable 3.28 and the value of Sig. 0.047 < 0.05.